Stop! Hammer time: rethinking our approach to rowhammer mitigations - Loughlin, Kevin; Saroiu, Stefan; Wolman, Alec; Kasikci, Baris (18th Workshop on Hot Topics in Operating Systems (HotOS), 2021)
Rowhammer attacks exploit electromagnetic interference among nearby DRAM cells to flip bits, corrupting data and altering system behavior. Unfortunately, DRAM vendors have opted for a blackbox approach to preventing these bit flips, exposing little information about in-DRAM mitigations. Despite vendor claims that their mitigations prevent Rowhammer, recent work bypasses these defenses to corrupt data. Further work shows that the Rowhammer problem is actually worsening in emerging DRAM and posits that system-level support is needed to produce adaptable and scalable defenses. Accordingly, we argue that the systems community can and must drive a fundamental change in Rowhammer mitigation techniques. In the short term, cloud providers and CPU vendors must work together to supplement limited in-DRAM mitigations—ill-equipped to handle rising susceptibility—with their own mitigations. We propose novel hardware primitives in the CPU's integrated memory controller that would enable a variety of efficient software defenses, offering flexible safeguards against future attacks. In the long term, we assert that major consumers of DRAM must persuade DRAM vendors to provide precise information on their defenses, limitations, and necessary supplemental solutions.